Traditional Leadership of Kasepuhan Ciusul, Citorek Village, Cibeber District, Lebak-Banten Regency - Fajriati, Nurul; Holisoh, Iis; Muttaqin, Ahmad; Jamaludin, Ujang (Universitas Syiah Kuala, 2024)
This study aims to analyze the structure, function, and role of traditional leadership in Citorek Village, especially in Ciusul Village, Cibeber District, Lebak Regency.The main focus of this research is to uncover the decision-making process carried out in the context of customary leadership and village government.Traditional leadership in Ciusul has a crucial role in maintaining the social and cultural balance of the local community.The method used in this study is a descriptive qualitative approach, with data collection techniques in the form of interviews, observations, and documentation analysis.The results of the study show that customary leadership contributes significantly to maintaining the culture and traditions inherited by previous ancestors, while the role of formal government in customary leadership is to support the sustainability and recognition of indigenous peoples.The existence of this collaboration is very effective in maintaining and preserving both culture and nature.This research provides insight into the sustainability of the customary leadership system in the midst of modernization and has the potential to contribute to the development of policies that support the preservation of local culture in Indonesia.